Konsep Kesehatan Jiwa dalam Pemikiran Ibn Miskawaih: Relevansinya terhadap Kesehatan Mental Generasi Z - Saepulah, Asep (Universitas Islam Negeri Imam Bonjol Padang, 2024)
This paper aims to examine the concept of Ibn Miskawaih's Mental Health in his work entitled Tahdzibul Al-Akhlaq and its relevance to the mental health of Generation Z. The writing method used in this study is a qualitative method in the form of a literature study with the primary book by Ibn Miskawaih entitled Tahdzib Al-Akhlaq which has been translated into Menuju Kesempurnaan Akhlak. In the process of analyzing the data, the author uses a descriptive-analytical analysis method. The results of this study indicate the conclusion that various mental health issues faced by Generation Z, as well as the relevance of mental health in Ibn Miskawaih's thinking, are expected to be the foundation for the formation of strong mental health. Because, for Ibn Miskawaih, mental health is a divine faculty, not physical, so that it can affect the activities of the mind and heart in everyday life. Especially for the mental health of Generation Z. This paper contributes to modern Islamic thought in understanding various mental problems of Generation Z scientifically which include attitudes and behavior both physically and mentally.